Hemolytic Anemia due to Right Ventricular to Pulmonary Artery Conduit Stenosis. Issue 5 (July 2017) - Rao, Sudha; Creaden, Julie A.; Gong, Shunyou; Rigsby, Cynthia; Costello, John M.
Abstract : Hemolytic anemia is a well-recognized complication in patients with left-sided mechanical heart valves. It is rare to see hemolysis with a bioprosthetic valve in the right ventricular outflow tract. We report a 4-year-old-girl with history of truncus arteriosus status-post repair who developed hemolytic anemia as a result of a calcified and obstructed bioprosthetic right ventricular to pulmonary artery–valved conduit. The hemolysis was alleviated by replacing the obstructed conduit with a larger valved conduit.